Theory of inventive problem solving based sector specific guidance for electrical engineers to seek innovative solutions systematically - Mansoor, Muhammad (2013)
Complexity of engineering systems is growing with integration of multiple technologies as one system. It is becoming hard for engineers to address problems in a system, which needs expertise in multiple technological domains. To cater this ever growing complexity, systematic guidance is a worthy assistance. To help engineers generate focused ideas, determine probable solution directions and foresee future developments in a sector, while providing systematic guidance is a valuable support. With the aim of supporting engineers to meet today’s challenges, this research used capabilities of TRIZ for development of sector specific guidance. The generated guidance is worked to be optimized for sub-domains of a major field. To reduce this complexity and facilitate engineers, TRIZ do offer a strong set of tools and methods. The approach of working out sector specific guidance for smaller sectors will open a window for new ideas, to seek future transitions of engineering systems in specific sector. It will also reduce need of a TRIZ expert in dealing a problem, while looking for TRIZ based solution guidance. Taking engineering solution design stages into consideration, this research aims for guiding engineers at conceptual design stage of solution hunting. A strong conceptual design will result in less design iterations, hence reducing time and cost of solution hunting process. With this aim, the research seeks to set a direction and methodology for ‘how to generate sector specific guidance framework’. The research successfully met all objectives to meet the aim of this research. For this purpose, the research worked out three cases from different sub-domains of electrical engineering. The chosen cases are significant topics in electrical power engineering now a day, i.e. sustainable energy development, asset management and dynamic voltage restorer (DVR) devices. To validate proposed methodology and resulted guidance framework, it executes an example of a real problem with help of developed guidance framework. Effective results are achieved by application of developed guidance framework, which validates research approach and methodology. Successful results achieved for development of systematic guidance are presented for all three cases.